Exploring the reuse of cooking and motor oils in cold forging processes - Eduardo Schmitzhaus , Tobias; da Conceição, Emmanuel Lemos; Schmitzhaus, Wagner Cristiano; Simoni, Leonardo (International Journal of Scientific World, 2024)
In contemporary industrial practices, the pursuit of sustainable manufacturing processes is imperative. Cold forging of aluminum, a versatile and widely used metal, relies heavily on lubrication to reduce friction and wear during deformation. Conventional lubricants, such as mineral oils, raise environmental concerns. Nevertheless, oils are common and essential products for manufacturing utensils in various sectors such as metallurgy, culinary, and automotive, among others. This study evaluates the lubrication performance of used cooking oil and old motor oil in aluminum cold forging, examining the surface finish, roughness, and compression test (tension vs deformation chart) flow, maximum deformation. Results indicate positive lubrication effects, with cooking oil showing the best performance when combined with graphite. Statistical analysis confirms significant differences in lubricant performance compared to dry forging. Visual inspection reveals smoother surface markings with lubricants, particularly cooking oil. Uniaxial compression tests demonstrate improved mechanical behavior with lubricants, especially when combined with graphite. Overall, lubricants enhance surface finish and mechanical properties, underscoring their potential for sustainable forging practices. The use of recycled oils like used cooking oil and old motor oil can contribute to a more environmentally friendly manufacturing process.